2017
DOI: 10.5152/iao.2016.1855
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cartilage Palisades and Temporal Fascia in Type 1 Tympanoplasty for Bilateral Tympanic Membrane Perforations in Children

Abstract: OBJECTIVE:To compare the graft success rates and audiological outcomes of bilaterally performed type 1 tympanoplasty using cartilage palisades or temporal fascia in children. MATERIALS and METHODS:We retrospectively analyzed the medical records of patients who underwent type 1 tympanoplasty at Medical Park Hospital between May 2007 and February 2013. 27 patients (54 ears) were enrolled in the study: 15 (30 ears) in the palisade cartilage group and 12 (24 ears) in the fascia group. RESULTS:The graft success rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Cartilage graft was taken in 43 cases (97.7%) in this study, which is comparable to other studies as listed in table below (Table-III) [1][2][3]7,[10][11][12][13][14][15][16][17][18]. …”
supporting
confidence: 83%
“…Cartilage graft was taken in 43 cases (97.7%) in this study, which is comparable to other studies as listed in table below (Table-III) [1][2][3]7,[10][11][12][13][14][15][16][17][18]. …”
supporting
confidence: 83%
“…Moreover, in another retrospective study comparing cartilage and temporal fascia graft in type 1 tympanoplasty for bilateral perforations in children, Gun et al [22] found no statistically significant difference between fascia and cartilage. The mean follow-up in the fascia group was 23.2 months, and that for the cartilage was 21.9 months.…”
Section: Discussionmentioning
confidence: 97%
“…After myringoplasty, the mean postoperative air-bone gap for medium, large and small perforations was 14.22 dB, 22.62 dB and 6.24 dB, correspondingly. According to the data, the average improvement in the air-bone gap or the increase in hearing for minor perforations was 5.24 dB, respectively [22][23] .…”
Section: Discussionmentioning
confidence: 97%